EFEK DUKUNGAN SELEBRITI, CITRA MEREK DAN KEPERCAYAAN MEREK TERHADAP MINAT BELI PELANGGAN INSTAGRAM - Yuaniko Paramitra; Nino Nopriandi Saleh (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2022)
The purpose of this study was to analyze the mediating effect of brand image and brand trust between celebrity endorsements and purchase intention of Instagram users. Respondents in this study were women Instagram users who followed Maudy Ayunda's Instagram as a marketing influencer for the pond's brand, the analytical method used was path analysis. The results of the study stated that the influence of celebrity support on Instagram users' purchase intention through brand image and brand trust was smaller than the direct influence of celebrity support on Instagram users' purchase intention.